2021
DOI: 10.1109/jeds.2020.3044112
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Granularity Effects in Electromigration

Abstract: The persistent advancements made in the scaling and vertical implementation of front-end-of-line transistors has reached a point where the back-end-of-line metallization has become the bottleneck to circuit speed and performance. The continued scaling of metal interconnects at the nanometer scale has shown that their behavior is far from that expected from bulk films, primarily due to the increased influence that the microstructure and granularity plays on the conductive and electromigration behavior. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Indeed, the high activation energy of 0.93 eV for the SAM-fully-passivated Cu interconnects suggests that their failure is primarily through EMinduced diffusion of Cu via either grain boundaries or grains. 28,33 As noted in Fig. 6, activation energies of both Cu(SAM) and Cu lines are gradually increased with annealing temperature.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Indeed, the high activation energy of 0.93 eV for the SAM-fully-passivated Cu interconnects suggests that their failure is primarily through EMinduced diffusion of Cu via either grain boundaries or grains. 28,33 As noted in Fig. 6, activation energies of both Cu(SAM) and Cu lines are gradually increased with annealing temperature.…”
Section: Resultsmentioning
confidence: 62%
“…Previous EM studies have suggested that relatively low activation energy values ranging from 0.50 to 0.65 eV are typical of Cu interconnects involving interface/surface diffusion. 29,32,33 Using a bamboo-like microstructure or a capping layer to block the fastest (interfacial/surface) diffusion routes further strengthens EM reliability of Cu interconnects and elevates the activation energies to typically 0.7-0.8 eV, characteristics of grain-boundary diffusion. 28,33,34 Moreover, adhesion is regarded as another important factor that decides the reliability of a metal interconnect line under EM testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This intricate network of components, Since interconnects ultimately serve as pathways for current transmission, it is necessary to minimize the heat generated by Joule heating resulting from current flow [11]. However, in situations requiring scaling down, the shrinking size of vias gradually has become a cause of current flow bottlenecks within the metal line, making them susceptible to Joule heating [12,13]. Therefore, this study utilized the finite element method (FEM) technique [14,15] to model interconnects in a simplified structure and conducted simulations to analyze the extent to which Joule heating, based on the area ratio between the metal line and via, affects the reliability of the interconnect.…”
Section: Methodsmentioning
confidence: 99%